2008
DOI: 10.1007/s12161-008-9064-x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Aflatoxins and Ochratoxin A in Baby Foods in Portugal

Abstract: Infants have a more restricted diet and they generally consume more food on a body weight basis than adults. Therefore, the significance and potential health risk of any contaminant in foods consumed by infants is increased and diligent attention must be paid to this particular area. The present study aims to determine the occurrence of aflatoxin M 1 (AFM 1 ), aflatoxin B 1 (AFB 1 ) and ochratoxin A (OTA) in processed cereal-based foods (flours) and infant formulae (milk powder) available in the Portuguese mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 10 publications
2
57
2
1
Order By: Relevance
“…The occurrence and level of AFM 1 in formula samples are in line with those revealed by other authors. Alvito et al (2010) demonstrated that AFM 1 was detected in 4 out of 27 baby foods purchased from big supermarkets, retail shops and pharmacies in Lisbon, Portugal, with a maximum level of 0.041 mg kg À1 . In a screening study carried out on infant formula milks in Italy, Meucci et al (2010) found that only two out of 185 samples contained detectable levels of AFM 1 (range ¼ 11.8e15.3 ng l À1 ).…”
Section: Occurrence Of Afm 1 and Otamentioning
confidence: 97%
See 1 more Smart Citation
“…The occurrence and level of AFM 1 in formula samples are in line with those revealed by other authors. Alvito et al (2010) demonstrated that AFM 1 was detected in 4 out of 27 baby foods purchased from big supermarkets, retail shops and pharmacies in Lisbon, Portugal, with a maximum level of 0.041 mg kg À1 . In a screening study carried out on infant formula milks in Italy, Meucci et al (2010) found that only two out of 185 samples contained detectable levels of AFM 1 (range ¼ 11.8e15.3 ng l À1 ).…”
Section: Occurrence Of Afm 1 and Otamentioning
confidence: 97%
“…Infants are a vulnerable part of the population due to, in part, their physiology, a fairly restricted diet and a higher consumption relative to their body (Alvito, Sizoo, Almeida, & van Egmond, 2010). There are many foods on the market today that are specifically manufactured for infants and young children aged between 1 and 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies include quantification of low molecular weight polyphenols in vegetables (Silva et al 2012), polycyclic aromatic hydrocarbons (PAHs) in fish (Ramalhosa et al 2009), acrylamide in food (Mastovska and Lehotay 2006), veterinary drugs (Brondi et al 2013;de Souza et al 2013), mycotoxins in grains (Kokkonen and Jestoi 2009) dried fruits (Azaiez et al 2014) and cereal products (Cunha and Fernandes 2010;Vaclavik et al 2010;Zachariasova et al 2010;Soleiman et al 2011;Ferreira et al 2012) as well as in other matrices (Alvito et al 2010;Bertuzzi et al 2012;Fernandes et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a representative food sampling design (selecting the most susceptible foods, considering a large set of individual and/or composite samples), an accurate chemical analysis method (with low detection limits) and a suitable method to manage left-censored data will be decisive to obtain realistic exposure estimations with low level of uncertainty. This could be particularly important for the exposure assessment of vulnerable population groups such as small children that are generally exposed to higher levels of mycotoxins than adults (Alvito et al, 2010;Assunção et al, 2015;Cano-Sancho et al, 2013;Sirot et al, 2013).…”
Section: Main Challenges In Exposure Assessment To Multiple Mycotoxinsmentioning
confidence: 99%